Aberrant degree centrality of functional brain networks in subclinical depression and major depressive disorder - Yang, Lei; Jin, Chaoyang; Qi, Shouliang; Teng, Yueyang; Li, Chen; Yao, Yudong; Ruan, Xiuhang; Wei, Xinhua (Frontiers in Psychiatry, 2023)
Background: Major depressive disorder (MDD) is a serious disease affecting about 10% of the global population. Subclinical depression (SD) provides an indicator of the risk of developing MDD. This study constructed a functional brain network and analyzed the degree centrality (DC) among MDD, SD, and healthy control (HC) groups. Methods: A total of 40 participants with MDD, 34 with SD, and 40 HCs matched by age, sex, and education were included. Resting-state functional magnetic resonance imaging(rs-fMRI) data were used to analyze DC. One-way analysis of variance and post-hoc t-tests were performed to identify brain regions with significantly different DC between the groups. Receiver operating characteristic curve analysis for single brain regions with significantly different DC values and regressed combined features was performed. Results: Compared with the HC group, patients with MDD showed increased DC in the right superior temporal gyrus (STG) and right inferior parietal lobule (IPL). Compared with the HC group, patients with SD showed increased DC in the right STG and the right middle temporal gyrus (MTG) and decreased DC in the left IPL. Compared with the SD group, the MDD group showed increased DC in the right middle frontal gyrus, right IPL, and left IPL, and decreased DC in the right STG and right MTG. ROC curves showed that the DC in the right STG could distinguish MDD from HC (AUC = 0.779); the DC in the right MTG could distinguish MDD from SD (AUC = 0.704). The three composite indexes had good discriminative ability in each pairwise comparison, with AUCs of 0.803, 0.751, and 0.814 for MDD vs. HC, SD vs. HC, and MDD vs. SD, respectively. Conclusion: Altered DC in the STG, MTG, IPL, and middle frontal gyrus were identified in patients with SD and MDD, and the DC values and their combinations presented good discriminative ability between HC, SD, and MDD. These findings provide insights into the potential pathophysiological mechanisms of SD and MDD.